Fungal Endophytes as Mitigators against Biotic and Abiotic Stresses in Crop Plants - H. G. Gowtham; P. Hema; Mahadevamurthy Murali; N. Shilpa; K. Nataraj; G. L. Basavaraj; Sudarshana Brijesh Singh; Mohammed Aiyaz; A. C. Udayashankar; Kestur Nagaraj Amruthesh (Journal of Fungi, 2024)
The escalating global food demand driven by a gradually expanding human population necessitates strategies to improve agricultural productivity favorably and mitigate crop yield loss caused by various stressors (biotic and abiotic). Biotic stresses are caused by phytopathogens, pests, and nematodes, along with abiotic stresses like salt, heat, drought, and heavy metals, which pose serious risks to food security and agricultural productivity. Presently, the traditional methods relying on synthetic chemicals have led to ecological damage through unintended impacts on non-target organisms and the emergence of microbes that are resistant to them. Therefore, addressing these challenges is essential for economic, environmental, and public health concerns. The present review supports sustainable alternatives, emphasizing the possible application of fungal endophytes as innovative and eco-friendly tools in plant stress management. Fungal endophytes demonstrate capabilities for managing plants against biotic and abiotic stresses via the direct or indirect enhancement of plants’ innate immunity. Moreover, they contribute to elevated photosynthesis rates, stimulate plant growth, facilitate nutrient mineralization, and produce bioactive compounds, hormones, and enzymes, ultimately improving overall productivity and plant stress resistance. In conclusion, harnessing the potentiality of fungal endophytes represents a promising approach toward the sustainability of agricultural practices, offering effective alternative solutions to reduce reliance on chemical treatments and address the challenges posed by biotic and abiotic stresses. This approach ensures long-term food security and promotes environmental health and economic viability in agriculture.